Strengthening HPV vaccination delivery: findings from a qualitative service evaluation of the adolescent girls' HPV vaccination programme in England. (20th June 2019) - Paterson, P; Mounier-Jack, S; Saliba, V; Yarwood, J; White, J; Ramsay, M; Chantler, T
Abstract: Background: In 2014, the number of HPV vaccine doses given to adolescent girls as part of the English school-based immunization programme was reduced from three to two. This was based on evidence that a two-dose schedule provides long-lasting protection against HPV infection. In 2015/16 a small decline in HPV vaccination coverage in adolescent girls was noted; from 86.7% for the three-dose schedule in 2013/14 to 85.1% for the two-dose schedule. This evaluation examined whether service-related factors contributed to this decline. Methods: In May–August 2017, we conducted semi-structured qualitative interviews with 39 participants responsible for commissioning or delivering immunization programmes in six local authorities in the South West, North Central Midlands and South Central Midlands, England. Results: Effective planning and data management were key for successful service provision of HPV vaccination, as well as close collaboration between commissioners, service providers and data system managers, a team skill mix with experienced staff, pro-active engagement with schools and service providers equipped to respond to parental concerns. Conclusions: To maintain and improve the high HPV adolescent girls' vaccine coverage rates achieved in England, in the context of an expanding school-based immunization programme, it is essential to strengthen the organizational capacity of the delivery system.